Nursing Students’ Perception of Online Learning Amidst COVID-19 Pandemic - Rana, Sunita; Garbuja, Chandra Kumari; Rai, Geeta (Journal of Lumbini Medical College, 2021)
Introduction: The declaration of COVID-19 pandemic on 11th March 2020 by World Health Organization forced many countries including Nepal to choose online mode of nursing education. Hence, it is essential for the educators to find out students’ perception that ensures their readiness to learn in this new environment. This study sought to examine the perception of online learning among nursing students. Methods: After obtaining ethical clearance, a cross-sectional descriptive study was conducted among 211 nursing students using enumerative sampling method. Self-administered structured online questionnaire was used. Calculated Cronbach's alpha value was 0.828. Descriptive (frequency, percentage, mean etc.) and inferential statistics (Chi-square test) were used to analyze data. Results: The mean age of the participants was 19.80±1.87 years. All (100%) had mobile phone. Most (93.8%) had internet facility at home. More than half (59.7%) strongly agreed that face-to-face learning was more effective. Less than half (44.6%) strongly agreed that interrupted internet connection was an obstacle. More than half (56.9%) participants had positive perception of online learning. Age, enrolled nursing program and device used were statistically significant with perception of online learning. Conclusion: The perception of nursing students towards online learning is positive. Students are satisfied with their learning opportunities amidst COVID-19 through online education. However, interrupted internet connection, unfeasible practical natured courses, load-shedding etc. were perceived as obstacles to online learning. Age, enrolled nursing program, academic year, and devices used had an impact on positive perception.